Integration of in situ and laboratory velocity measurements: analysis and calibration for rock formation characterization - Isham, Randi Jo Lee (Kansas State University, 2012)
In this study, laboratory measurements of ultrasonic frequency P- and S-wave velocities were collected and analyzed from two sets of cores. The first set is from a near surface study in southeastern Kansas, and the second set was from the deep subsurface and obtained from a newly drilled well (Wellington KGS 1-32) in Sumner County, KS. Ultrasonic velocities acquired from the second set of cores were then compared with in situ sonic and dipole sonic frequencies of P- and S-waves from well logs. Well log data, core data, and ultrasonic velocity measurements were integrated for Gassmann fluid replacement modeling. The understanding of the velocity and elastic moduli variations at ultrasonic frequencies, along with the comparison of well log velocities can potentially provide improved understanding to establish a beneficial calibration relationship. It could also allow for estimation of shear wave velocities for wells lacking dipole sonic log data. The ability to utilize cost-effective ultrasonic measurements of velocities and elastic moduli in the laboratory, for fluid replacement modeling (Gassmann) in CO[subscript]2-sequestration, as well as, enhanced oil recovery (EOR) projects, would be a significant advance. Potential alternative use of ultrasonic velocities for determining the effects of fluid replacement using Gassmann modeling, when log data is lacking, is an ongoing effort. In this study, the fluid replacement modeling is executed based on sonic and dipole sonic P- and S-wave velocities and compared with results from theoretical modeling. The significance of this work lies in the potential of establishing a calibration relationship for the representative lithofacies of the carbon geosequestration target zone of the Wellington KGS 1-32 well in Sumner County, and enabling the use of ultrasonic measurements of body wave velocities and elastic moduli in Gassmann fluid replacement modeling. This work, when integrated with continuing effort in mapping lithofacies of the Arbuckle and Mississippian groups, would potentially be of great importance to fluid flow simulation efforts and time-lapse seismic monitoring. This study will utilize Gassmann modeling and a range of measurements and data, which include: well logs and ultrasonic laboratory P- and S-wave measurements and core analysis data.
Keywords: Ultrasonic velocity measurements; Rock formation characterization; Comparison; In situ measurements; Laboratory measurements; Kansas; Geology (0372); Geophysics (0373)